Position Synchronization Control Algorithm of Legged Robot Based on DSP Centralized Control - Ma, Li (Mobile networks and applications, 2022)
When the traditional RRT algorithm is used to control the position of the legged robot synchronously, its adaptability is poor and it is easy to be disturbed by the surrounding environment, which leads to the low stability of the robot when avoiding obstacles. The position synchronization control algorithm of the legged robot based on DSP centralized control is proposed. The parameter on-line fuzzy self-tuning PID algorithm is used in the position loop of the control system of the robot car controller to improve the adaptive ability of the robot. The inverse Fourier transform of cross power spectrum is used to determine the position and orientation angle of the robot, and the displacement theorem of the robot is used to control the position of the robot synchronously. The experimental results show that the proposed algorithm can effectively synchronize and control the robot running safely and accurately in obstacle-free environment. The average time is 18 s, the maximum robustness is 0.45, and the maximum control error rate is 0.25. It has the advantages of high control efficiency, high robustness and small error, which ensures the stable operation of the robot.